Advanced oxidation processes (AOPs)-based sludge conditioning for enhanced sludge dewatering and micropollutants removal: A critical review. (February 2022) - Lin, Wei; Liu, Xiao; Ding, An; Ngo, Huu Hao; Zhang, Rourou; Nan, Jun; Ma, Jun; Li, Guibai
Abstract: Applying advanced oxidation processes (AOPs) in sludge dewatering to improve sludge treatment, disposal and environmental protection has attracted much interest due to the difficulties arising in extracellular polymeric substances (EPS) degradation during the sludge dewatering process. Oxidants can produce different types of free radicals and exert specific oxidation effects through different action mechanisms on water saturated sludge. This plays an important role in sludge dewatering, sludge minimization and removal of different types of micropollutants and/or their transformation. The current review critically evaluates the role of AOP in improving the efficiency of sludge dewatering. Characteristics of advanced oxidation methods applied to sludge dewatering are systematically illustrated through different mechanisms using free radical reactions and various sludge dewatering conditions. Factors which impact on influencing the minimization of sludge and removals of typical micropollutants during the sludge conditioning process are also analyzed. Finally, applications of advanced oxidation methods in the future are proposed based on a technoeconomic analyses of dewatering efficiency and operation cost. This review provides theoretical support regarding the application of advanced oxidation processes in sludge dewatering and avenues for practical engineering. In the current review, it is determined that the efficiency of AOP for the improvement of sludge dewatering, micropollutants removal and sludge minimization in the treatment and disposal of sludge have been fully investigated. Unfortunately, there is still lack of comparing the ability of different free radicals on published review. Graphical abstract: Unlabelled Image Highlights: AOP-based sludge conditioning for enhanced sludge dewatering is reviewed. The function of different radicals is evaluated. Different radicals for micropollutants removal are analyzed. Economic considerations of different AOP methods are materialized.